LAYER STRUCTURE MAPPING BELOW THE SURFACE USING SPATIAL AUTOCORRELATION METHOD - Nadhika Saifullah, Kahfi
Mechanical waves that propagate on earth are one of the media that can be used to observe the structure of rock or soil layers inside the earth. One type of wave that can be used to measure the layers structure inside the earth is Rayleigh waves. One method that can be used to find characteristics of Rayleigh waves is the microtremor survey method. This method can provide the structure of rock layers inside the earth using Rayleigh wave characteristics that can be obtained from recorded microtemor data. In this study, data was recorded in Civil Engineering field, Bandung Institute of Technology. Data was recorded on July 7, 2019 using two geophone with each having accuracy of 1 Hz and 5 Hz. Each measurement was carried out at 9 points spread over three layers of array with circular shapes. The first layer has a radius of 50 meters, the second layer with the radius of 25 meters and the third layer with radius of 12.5 meters. Data was recorded for approximately 8 to 10 minutes each. The results are processed using Matlab and Geopsy software. The result obtained are autocorrelation coefficient values graph, dispersion curves, and Shear wave velocity to depth distribution graph. Based on Shear wave velocity distribution graph, it is known that from surfave until the depth of 150 meter below the surface has one type of layer.